Study of healing effects of the “Fomitop” gel on artificial burn wounds (Mongolian Journal of Agricultural Sciences, 2021)
As a result of previous studies, we have established the “Fomitop” gel with extracts from the fungus Fomitopsis officinalis has antibacterial properties against some strains such as Staphylococcus aureus, Micrococcus luteus, Bacillus subtilis, and Enterococcus faecalis. Based on these results, we have conducted this research to identify the “Fomitop” gel has a healing effect on the burn wound. For this purpose, were conducted the comparative analysis of healing effects of the “Fomitop” gel with the standard ointment - silver sulfadiazine cream, on artificial burn wounds created on the back skin of a mouse. Total 27 Balb/c mice were included in the experiment and they are divided into three equivalent groups. In the first treatment, the group was applied to the “Fomitop” gel, the second standard group was applied silver sulfadiazine cream, and the third control group untreated by any ointment. On the 1, 5, 12, 21, and 35th days after wound creation, were taken the histological samples from the wound and near areas of the wound. The wound healing process was evaluated based on histological analysis. The burn wounds of the treatment group of mice (applied “Fomitop” gel) fully healed on the 33rd day of the experiment. While the wound healing rate of the standard group of mice (applied silver sulfadiazine cream) was 92.2% on the same day. And the control group mice wound healing rate was 78% (p